The Correlation Between Math Anxiety Level and Numeracy Skills of Fifth-Grade Students - Maghfira, Deanita; Husni, Muhammad; Aziz, Abdul (Sumber Belajar Sejahtera, 2024)
This study aims to determine the correlation of math anxiety to numeracy skills. The sample in this study was one class, namely class V at 5 Elementary School Selong with a total of 27 people. The research design used is correlational with quantitative research type. The results of the validity and reliability tests stated that there were 17 valid and highly reliable math anxiety questionnaire statement items and there were 20 valid and reliable numeracy test items. To analyze the data, researchers used the Person Product Moment correlation which previously conducted a normality test manually with the help of excel using the Saphiro Wilk formula. Based on data analysis, the calculation of the variable relationship is -0.40. This means that math anxiety with numeracy skills is a negative correlation. Based on the interpretation of the correlation coefficient, the relationship between the two variables is in the moderate category. The amount of contribution of math anxiety variables to numeracy skills is 16% and 84% is determined by other variables. After that, the significance test is carried out with the T-test, then seen from the hypothesis testing criteria, namely obtained tcount = -2.17 while ttable (5%) = 2.06. From the calculation results, it can be seen that the result of tcount = -2.17 < ttable = -2.06. This shows that H0 is rejected and H1 is accepted. So it is concluded that